Safety and Efficacy of Percutaneous Nephrolithotomy in Patients with Severe Skeletal Deformities - Mousavi-bahar, Seyed Habibollah; Amirhasani, Shahriar; Mohseni, Maede; Daneshdoost, Rezgar (Urology Journal, 2017)
Purpose: Treatment of renal calculi in patients with severe skeletal deformities can be challenging. We present our experience in order to provide an assessment of technical difficulties, associated complications, and outcomes of percutaneous nephrolithotomy (PCNL) as a treatment option in this special patient group. Materials and Methods: Our study included eight patients treated with PCNL for renal stones. All had severe skeletal deformities including six with severe kyphoscoliosis, one with osteogenesis imperfecta, and another with rickets. After pre-operative evaluation the procedure was performed under fluoroscopic and/or ultrasonic guidance. In all but one case, PCNL was performed with the patient in the prone position. Silicone rolls and soft padded bolsters were used to obtain the best positioning for the procedure. Clearance rates and complications were assessed. Results: Complete stone-free rate was achieved in six patients (75%) after first-PCNL. The two patients with residual stones underwent a second-look PCNL, after which one was completely cleared. The overall complete stone-free rate after second PCNL was 87%. Only minor complications were seen in two patients (25%). Conclusion: We found PCNL to be safe and effective for managing kidney stones in patients with severe skeletal deformities.